Synthesis and Luminescence of 4H-Benzo[b]pyran Derivatives Catalyzed by Silica Sulfuric Acid in Aqueous Media - Wan, Yu; Liu, Wan-wan; Zhan, Qi-chen; Cui, Hao; Zhang, Qian; Yue, Shu-ning; Lin, Wei; Zhou, Sheng-liang; Wu, Hui (Letters in Organic Chemistry, 2015)
Silica sulfuric acid (SSA) was used as efficient catalyst for the synthesis of 4Hbenzo[ b]pyran derivatives via the one-pot three-component condensation of aromatic aldehyde (1), 5,5-dimethyl-1,3-cyclohexanedione (2a) or 1,3-cyclohexandione (2b) and malononitrile (3) in aqueous media with high yields. The luminescence of products was studied in detail.
Keywords: Synthesis